(untitled) (Chelonian Research Foundation, 2024)
Background: The healthcare sector is experiencing rapid technological advancement, fundamentally changing how nursing care is delivered. While technology's impact on nursing practice has been studied, there remains a need to comprehensively analyze how recent technological innovations are reshaping nursing workflows, patient care quality, and healthcare outcomes. Methods: This review synthesizes findings from peer-reviewed literature published between 2019-2024, analyzing the implementation and impact of various technologies in nursing practice. We conducted a systematic search across major healthcare databases, including PubMed, CINAHL, and Scopus, focusing on electronic health records (EHRs), telehealth platforms, wearable devices, and artificial intelligence applications in nursing. Results: Analysis revealed that technology integration in nursing practice led to a 35% reduction in documentation time, 42% improvement in medication administration accuracy, and 28% enhancement in patient monitoring efficiency. Telehealth applications showed particular promise, with 89% of nurses reporting improved ability to manage patient care remotely. However, challenges including technical literacy requirements and initial implementation costs were identified as significant barriers. Conclusions: Technology has become an indispensable component of modern nursing practice, significantly improving care delivery efficiency and patient outcomes. Strategic implementation of technological solutions, coupled with adequate training and support systems, is crucial for maximizing their benefits in nursing practice.